(2,9-Dimethyl-1,10-phenanthroline)bis[2-(pyridin-2-yl)phenyl]iridium(III) hexafluorophosphate and (2,9-dimethyl-1,10-phenanthroline)bis[5-methyl-2-(pyridin-2-yl)phenyl]iridium(III) hexafluorophosphate–diethyl ether–acetonitrile (1/0.61/0.78) - Trevor J. Gienau; Malachi Clay; William W. Brennessel; Carly R. Reed (Acta Crystallographica Section E: Crystallographic Communications)
The title compounds, [Ir(C14H12N2)(C11H8N)2]PF6 (1) and [Ir(C14H12N2)(C12H10N)2]PF6·0.61C2H10O·0.78CH3CN (2), crystallize in the space groups Pbca and P1, respectively, each structure containing one monocationic Ir complex and one PF6− anion in the asymmetric unit. The anion and solvent in compound 2 are disordered. The Ir—N(phenanthroline) bond lengths of ca. 2.21 Å indicate a greater steric effect of the 2,9-dimethyl-1,10-phenanthroline ligand compared to 1,10-phenanthroline. Both structures show offset parallel intermolecular π–π interactions between the pyridine rings of the phenanthroline ligands, and that of 1 also exhibits similar interactions between the phenyl and pyridine rings of the phenylpyridine ligands.